Market-supporting institutions and effects of foreign direct investment, inflation, and inflation volatility on economic growth - Slesman, Ly (2014)
This thesis aims to empirically examine contingent roles Market Supporting Institutions (MSI) play in mediating the effects of standard Solow-Mankiw-Romer-Weil (Solow- MRW) growth determinants, Foreign Direct Investment (FDI), and inflation and inflation volatility on long-run economic growth. It uses the sample of 93 developed, emerging market and developing countries over 1980-2010 periods. In the first objective, it examines the role of market creating institutions (MCI), the core component of MSI, in indexing different growth regimes. Using Rodrik’s (2000, 2005)conceptualization to unbundle MSI into MCI, market-regulating (MREGI), marketstabilizing (MSTABI) and market-legitimizing (MLEGI) institutions, it investigates whether countries belong to regime with high MCI quality have efficiently transformed Solow-MRW growth determinants into higher growth compare with low quality MCI regime. Within this context, it also investigates whether MREGI, MSTABI, and MLEGI have differential growth effects in high- and low-MCI regimes. This is to test the contention that different institutions are inter-related in equilibrium whole, with any changes in one domain may influence the rest of domains—the so-called “institutional complimentarity hypothesis”. Recent existing literature overwhelmingly focuses on direct effects of “cluster” institutions on growth largely ignoring the indirect or indexing role of institutions and the interaction effects between different dimensions of institutional matrix in influencing long-run growth process. This objective seeks to fill this gap. In the empirical assessment, it uses a novel threshold regression method that is flexible in allowing the effects of growth determinants to take values depending on whether countries obtain the quality of MCI surpass above or fall below the unknown threshold value. The finding reveals that countries obtaining MCI quality above an estimated optimum threshold value (i.e. high-MCI regime) can transform Solow-MRW growth determinants and MREGI into higher growth than those falls below (i.e. low-MCI group). It finds weak support for MSTABI and no support for MLEGI that they each matter differently in low- and high-MCI regime. These findings are invariant to extensive robust tests. One important policy implication is that poor countries can have high productivity gains from factor inputs and efficient functioning of regulatory institutions from sufficient improvement in the quality of MCI. Next, there are various gaps exist in the literature on institutions, FDI and growth. First,evidences on FDI-growth link are highly inconclusive. Second, recent research stresses on prominent role of institutions in explaining paradox pattern of foreign capital flows—i.e. so-called “Lucas paradox”. Third, various local absorptive capabilities are found to play important roles in FDI-induced positive spillovers on growth. Fourth, recent studies that focus on local absorptive capacities do not distinguish the contrasting experience of developed and developing countries with respect to FDI and institutional infrastructure. Fifth, the MSI absorptive capacities have not yet been explored on FDIgrowth link. To link and fill these gaps, the objective two of this study examines the mediating role of MSI on growth effects of FDI in both developed and developing countries. It applies generalized method of moments system (S-GMM) estimators that are capable of controlling for country specific effects and endogeneity problems of all independent variables in a dynamic panel growth framework. The following results reveal. First, FDI does not have any direct significant effect on economic growth in all samples—i.e. full sample, and developed and developing country subsamples—under study but generally contingent on the levels of MSI. It shows MSI mediates positive impact of FDI on growth in both developed and developing economies. It fails to find any such evidence when both groups of countries are lump together in the full sample. Second, result also reveals that developed economies have all moved beyond a minimum threshold score on MSI in absorbing the positive spillovers from FDI on growth. Contrary to developing economies where a minimum threshold scores on MSI are needed before positive effects of FDI on growth kicks in. These findings are robust to a number of sensitivity checks. One optimistic policy implication is that less developed economies can gain relatively huge welfare benefit from FDI spillovers by upgrading their MSI quality to a certain (relatively low) optimum level. Finally, some scholars recently conjecture that weak institutions are the root cause of bad policy outcome and volatility. Their view stresses that Washington consensus of getting policy right must be complemented by getting institutions right. Existing literature seems to be silent on whether the data supports such contentions. The final objective of this thesis contributes to the literature in investigating the contingent roles MSI play in the growth effects of inflation and inflation volatility in a dynamic panel growth model. Using S-GMM on a dynamic panel growth model, it uncovers the following results. First, it does not find any evidences for the full sample but only for emerging market and developing countries (i.e. non-OECD economies) in supporting the contention that MSI and some of its components mediate the growth effects of inflation and inflation volatility on growth. These findings are robust to a number of sensitivity checks. Developing and emerging countries can have larger welfare gains from efforts to improve qualities of MSI through its reducing effects on growth cost of inflation and inflation volatility.